Calculating Thin Film Strain From XRD Data: Menghitung Regangan Film Tipis dari Data XRD - Shelan Salm Sadiq Qadr (Academia Open, 2023)
This study aims to investigate the crystallite size and microstrain of Cu plate samples subjected to various hot water treatment times using the Williamson-Hall method and XRD profiles. The estimated crystallite sizes obtained from this method were compared with scanning electron microscope (SEM) observations, showing good agreement. The Williamson-Hall method was also utilized to determine microstrain, and the influence of temperature on the mechanical properties of copper was examined, highlighting the dominant role of dynamic softening mechanisms in copper deformation. Line broadening analysis was employed to compare crystallite size and microstrain, demonstrating the usefulness of the Williamson-Hall method in cases where both factors contribute to line broadening. The research underscores the reliability of the Williamson-Hall method in accurately determining crystallite size and microstrain from XRD line broadening analysis. The findings reveal that increasing treatment time leads to higher strain in thin films, and the calculated crystal size aligns well with reference measurements. This study provides valuable insights for designing and synthesizing copper-based materials with improved structural integrity and desired mechanical properties. Highlights: Accurate characterization: The Williamson-Hall method and XRD profiles are reliable techniques for determining crystallite size and microstrain in Cu plate samples, validated by comparison with SEM observations. Temperature influence: Temperature plays a crucial role in the mechanical properties of copper, with dynamic softening mechanisms dominating the deformation behavior. Line broadening analysis: Line broadening analysis allows for the comparison of crystallite size and microstrain, demonstrating the utility of the Williamson-Hall method in cases where both factors contribute to line broadening.